O magicznym czarze pewnej głoski - Wacławek, Maria (Paidia i Literatura, 2019)
The correct pronunciation of [č] sound is one of the most difficult problems in articulation that arises in the last period of speech development among children. Be it nursery rhymes or other rhymed texts, the orthophonic games and activities supposed to evoke this sound and develop articulation include the words of fairy‑tale origins; not only do they contain and exercise the aforementioned sound, but also they point to the theme that is liked and highly regarded by children. In addition to the brief analysis of this issue, the chapter presents some of the games and activities that might facilitate acquisition and processing of the correct pronunciation of the aforementioned “magical” sound.